2011
DOI: 10.1177/1091142111403620
|View full text |Cite
|
Sign up to set email alerts
|

The Income Elasticity of Lottery: New Evidence from Micro Data

Abstract: The authors analyze consumer expenditure on the National Lottery in Spain, a popular game with over 100 draws per year and annual turnover of about three billion euros. Based on Tobit estimates using data from two nationally representative surveys, National Lottery players tend to be middle-aged married males with relatively low education. In contrast to previous research, the authors find a strong relationship between lottery expenditure and income, with estimated income elasticities of more than one. A param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 24 publications
(49 reference statements)
3
29
1
Order By: Relevance
“…This result suggests that the illegal lottery "tax" exhibits a progressive trend and imposes a greater burden relative to income on the relatively rich than on the relatively poor among migrant workers. This differs from the evidence of a regressive legal lottery tax found in many other countries (Hansen 1995;Price and Novak 2000), but is similar to the case of Spain, where, in contrast to previous research on the legal lottery in developed countries, a strong rela tionship was observed between legal lottery expenditure and income, with an estimated income elasticity higher than one (Perez and Humphreys 2011). While legal lotteries can be viewed as implicit taxes contributing to government revenue from a public finance perspective (Clotfelter and Cook 1987), in the illegal lottery in China, it is the bookies that have benefited from participation of higher income punters.…”
Section: {Continued)contrasting
confidence: 60%
“…This result suggests that the illegal lottery "tax" exhibits a progressive trend and imposes a greater burden relative to income on the relatively rich than on the relatively poor among migrant workers. This differs from the evidence of a regressive legal lottery tax found in many other countries (Hansen 1995;Price and Novak 2000), but is similar to the case of Spain, where, in contrast to previous research on the legal lottery in developed countries, a strong rela tionship was observed between legal lottery expenditure and income, with an estimated income elasticity higher than one (Perez and Humphreys 2011). While legal lotteries can be viewed as implicit taxes contributing to government revenue from a public finance perspective (Clotfelter and Cook 1987), in the illegal lottery in China, it is the bookies that have benefited from participation of higher income punters.…”
Section: {Continued)contrasting
confidence: 60%
“…This dummy variable takes the value of 1 whenever the household is the proprietor of its house or flat and 0 otherwise. Finally, empirical evidence suggests that education has an influence on gambling behavior (see, e.g., Lutter 2009, forthcoming, andPerez andHumphreys 2011). The EVS data allows us to incorporate information on educational levels into our econometric analysis.…”
Section: Econometric Analysismentioning
confidence: 99%
“…The prior empirical literature on lottery play has largely been concerned with the question about its potential regressivity (see, e.g., Beckert and Lutter 2009, Clotfelter and Cook 1987, Crowley et al 2012, Farrell and Walker 1999, Perez and Humphreys 2011, Worthington 2001. 5 Our findings support the previous studies in that the income elasticity of expenditures on gambling is strictly less than one in all of our empirical models.…”
Section: Relation To Literaturementioning
confidence: 99%
“…Moreover, there is evidence in the financial domain to suggest that lower-income individuals spend a greater proportion of their incomes on state-run lotteries than higher-income households (see, for example, Clotfelter and Cook (1989);Oster (2004)), and that lottery participation is negatively related to educational attainment (Clotfelter and Cook, 1989;Perez and Humphreys, 2011). 3 3 A particular intriguing strain in the literature has explored a genetic explanation of the relationship between ability and risk aversion.…”
Section: A N U S C R I P Tmentioning
confidence: 97%